The Influence of Supervision, Leadership Style, and Motivation on Primary School Quality - Wulandari, Bevy Prihastuti; Ginting, Rosalina Br; Prayito, Muhammad (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of academic supervision, school principal leadership style, and teacher work motivation on the quality of education in primary schools (SD) in Bergas District, Semarang Regency. This research employs a quantitative approach with a survey design. The sample consists of 180 teachers selected using proportional random sampling from 28 public and 3 private primary schools in Bergas District. Data were collected through questionnaires measuring the variables of academic supervision, school principal leadership style, teacher work motivation, and school quality. Data analysis was conducted using multiple regression to test the influence of the independent variables on the dependent variable. The results show that academic supervision, school principal leadership style, and teacher work motivation significantly affect the quality of education in primary schools in Bergas District. Academic supervision has the greatest influence, contributing 86.4%, followed by the school principal leadership style (82.3%) and teacher work motivation (61.4%). Together, these three variables explain 92.6% of the variation in school quality. This study suggests that school principals should improve the planning of more structured academic supervision, enhance interpersonal relationships with teachers, and strengthen teacher motivation through external rewards and professional development training. These findings provide practical implications for educational policymakers and school leaders to prioritize and implement strategies that can significantly improve the quality of education in primary schools.